Examining the world's leading sport systems. How governance is structured (Project Play of the Aspen Institute, 2023)
The Aspen Institute conducted a review of the sport governance structures in the United States and 11 peer countries. Nations selected were based on geographic, cultural and economic factors, as well as upstream performance in the Olympics and other international events. Our focus was on both process and results, with grades given for Youth Sport Participation based on the percentage who play and for Government Support based on expert assessments.